(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
Militarization[1] in this country Mexico is a fundamental factor of political definition due to the loss of life[2] that it has represented, and the impact on public life stemming from the constant violation of the human rights of men, but especially for women, who have both seen their everyday life modified. This fight against organized crime, some have defined it as a war against the people, which pretends to be a war on drug trafficking. In Ciudad Juarez, we already know that the presence of the army and police on the streets does not increase safety, and instead, gender violence is exposed in deaths that occur constantly, so that militarization and impunity are the key to reading the new events as part of a hegemonic project, in which the bodies and humanity are no longer relevant.